Probing the affinity, selectivity and inhibition of ubiquitin-ubiquitin binding domain complexes by electrospray ionization mass spectrometry - Sokratous, Kleitos (2013)
This thesis describes the development and application of a rapid and sensitive electrospray ionization-mass spectrometry (ESI-MS) method to study the weak hydrophobic interactions seen in many Ub-Ub-binding domain (UBD) complexes. A range of UBDs has been screened against mono-Ub, di-Ub (Ub2) and tetra-Ub (Ub4). Affinities in the 2-200 J.lM range were found to be in excellent agreement with data obtained from other biophysical techniques. Insights into the UBD's preference for poly-Ub chain linkage and length are also provided by this methodology. Detection of a ternary complex involving Ub interacting simultaneously with two different UBDs demonstrated the co-existence of multisite interactions. A simple, clean and effective method for reducing charge states observed in ESI-MS without the use of any solution additives or instrumental modifications is also reported; with the charge reduction method ultimately promoting the investigation ofthe Ub-UBD interactions. Moreover, the development and application of a top-down proteomics approach to characterize the topology of an unanchored Ub dimer purified from rat skeletal muscle is also described in this thesis. This study has identified the topology of the Ub2 to be Lys48-linked. In addition, ESI-MS of endogenous Ub2 species has revealed the presence of cyclic Lys48-linked Ub2 and demonstrates for the first time that cyclisation of poly-Ub can also occur in vivo. Further to these studies, the inhibitory activity of small peptides against the complex formed by Ub with the ZnF domain of isopeptidase T (IsoT) is also investigated. Finally, the unusual effects of cation adduction upon the gas-phase conformation of three-helix bundle UBDs are revealed by ESI-IMS-MS and reported in this thesis.